2014
DOI: 10.3762/bjnano.5.23
|View full text |Cite
|
Sign up to set email alerts
|

Oriented attachment explains cobalt ferrite nanoparticle growth in bioinspired syntheses

Abstract: SummaryOriented attachment has created a great debate about the description of crystal growth throughout the last decade. This aggregation-based model has successfully described biomineralization processes as well as forms of inorganic crystal growth, which could not be explained by classical crystal growth theory. Understanding the nanoparticle growth is essential since physical properties, such as the magnetic behavior, are highly dependent on the microstructure, morphology and composition of the inorganic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…These types of interactions occur because the distance between charged amino acids is similar to the distance between atoms in the crystalline structure. This mechanism has been invoked to explain the control over size and morphology of magnetite nanocrystals by the C-terminal region of Mms6 (Arakaki et al 2003;Prozorov et al 2007;Wolff et al 2012Wolff et al , 2014. Since the structure of MamC remains unknown, to determine whether the observed effect of MamC correlates only with its net negative charge at the pH of the biomineralization experiments, or it is somehow more specific, we used several reference proteins of comparable molecular weight but different values of pI, so they will have a different net charge compared to that of MamC at the pH of the experiments.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These types of interactions occur because the distance between charged amino acids is similar to the distance between atoms in the crystalline structure. This mechanism has been invoked to explain the control over size and morphology of magnetite nanocrystals by the C-terminal region of Mms6 (Arakaki et al 2003;Prozorov et al 2007;Wolff et al 2012Wolff et al , 2014. Since the structure of MamC remains unknown, to determine whether the observed effect of MamC correlates only with its net negative charge at the pH of the biomineralization experiments, or it is somehow more specific, we used several reference proteins of comparable molecular weight but different values of pI, so they will have a different net charge compared to that of MamC at the pH of the experiments.…”
Section: Discussionmentioning
confidence: 98%
“…A majority of the published studies thus far involved the Mms6 protein, with the effort focused on in vivo analysis of Δmms6 mutants (Tanaka et al 2006) and in vitro experiments carried out with the full-length Mms6 and its C-terminal peptide (Arakaki et al 2003(Arakaki et al , 2010Amemiya et al 2007;Prozorov et al 2007;Wolff et al 2012Wolff et al , 2014. Results from these studies showed that Mms6 affects the size and morphology of magnetite crystals and that magnetites formed from solutions containing recombinant Mms6 protein were uniform well-defined crystals of~30 nm in size.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Materials characterization techniques are typically aimed at direct observations of the magnetite nucleation and growth at high spatial resolution. High resolution TEM is often used to observe formation of magnetosomes in magnetotactic bacteria via cryogenic TEM (cryo-TEM) 4,[22][23][24][25][26][27][28][29] . This technique provides vital information about organization of the cellular structures and development of the magnetosomes 20,27 .…”
mentioning
confidence: 99%
“…The "freeze and look" approach proved a very effective tool for evaluation of the complex synthetic pathways, notably the biomimetic formation of the nanoscale magnetite [165][166][167][168][170][171][172][173][174][175][176]. Importantly, the mechanism of biomimetic iron oxide formation remains unclear, largely because the analysis of the formed biomimetic solid is carried out either postsynthesis [6,21,22,34,44,78,177] or is performed on aliquots sampled during different stages of the growth process [165,166,171,173,[178][179][180][181][182]. Such an approach reveals the overall effect of the templating molecule and permits facile characterization of a biomimetic iron oxide; however, it generally lacks information about the dynamics of the material's formation.…”
Section: The Near In Situ Approachmentioning
confidence: 99%